Phytogeographical and sociolinguistical patterns of the diversity, distribution, and uses of wild mushrooms in Côte d'Ivoire, West Africa - Bakary Soro; N'golo Abdoulaye Koné; Linda Patricia Louyounan Vanié-Léabo; Souleymane Konaté; Adama Bakayoko; Daouda Koné (BMC, 2019)
Abstract Background Many fungal species in tropical Africa are useful, with high added value, and play essential roles in the structure and dynamic of ecosystems. However, the diversity, distribution, and uses by local populations of these non-timber forest products (NTFPs) and their respective habitats are still very poorly understood in sub-Saharan Africa in general and more specifically in Côte d'Ivoire. This study aims at (i) inventorying the wild useful mushrooms of Côte d'Ivoire within its major protected areas and their respective surrounding sociolinguistical groups, according to climatic and phytogeographical gradients, and (ii) recording ethnomycological knowledge and considerations of these local people. Methods Field and ethnomycological surveys were conducted in the main and highest protected areas of Côte d'Ivoire (Comoé, Marahoué, and Taï national parks) and a set of their respective surrounding villages, along climatic and phytogeographical gradients. Standardized methods (permanent plots and opportunistic searches) were used for field surveys. In addition, a total 748 respondents belonging to 13 ethnic groups were interviewed at a rate of 300 interviewees during the preliminary investigations and 448 persons during the proper ethnomycological surveys. Results Sixty-eight useful wild fungal species, belonging to 17 families and 23 genera, were listed and collected. Four categories of usage were reported by the rural people (food, medicinal, belief and recreational), with a dominance of food and medicinal uses. Fifty-six species were reported to be used as food and 16 species as medicinal fungi. These uses varied not only from one sociolinguistical group to another but also from a visited village to another. The high number (41) of the reported useful species was found in the Sudano-Guinean savanna zone while 28 species were collected in the forest zone and 22 species in the forest-savanna mosaic zone. These mushrooms were either saprotrophic or symbiotic (ectomycorrhizal or termitophilic). Auricularia sp3, Psathyrella tuberculata, and Termitomyces spp. were found as the most commonly used mushrooms. Conclusions These national scale field and ethnomycological surveys give one of the more complete but non-exhaustive list of useful mushrooms of Côte d'Ivoire. Mushrooms are relatively well known and used by the Ivorian people within the main phytogeographical zone of the country. These people also have an interest in all the functional groups with an important phytogeographical zone-fungal-specific used species. However, protected areas of the visited zones seem to represent the last sanctuaries of these organisms due to high rate of loss of natural habitats.